Taking La Lucha to Heart ll - Bundang, Rachel (Feminist theology, 2011)
This essay is a version of a presentation given at a session of the American Academy of Religion annual meeting in 2009, celebrating the work of Cuban-American theologian and ethicist Ada María Isasi-Díaz. The author traces the development of Isasi-Díaz’s work articulating Mujerista Theology and connects it with her own work as a Filipina in the United States developing Asian/ Pacific American Feminist Theology by pointing to 1) the intellectual kinship of having been formed in similar circles and circumstances and 2) the shared cultural citizenship of having emerged from a Catholicism that was the particular legacy of Spanish colonialism. Grounded in the faith lives of Latinas, Isasi-Diaz’s theo-ethical perspective grows out of a grassroots yet globally-minded Catholicism in conversation with both Feminist and Womanist theologies. She remains committed to Latinas as her primary community of accountability.